Catecholaminergic polymorphic ventricular tachycardia. An important diagnosis in children with syncope and normal heart - Leite,Luiz Roberto (2001)
Syncope in children is primarily related to vagal hyperreactivity, but ventricular tachycardia (VT) way rarely be seen. Catecholaminergic polymorphic VT is a rare entity that can occur in children without heart disease and with a normal QT interval, which may cause syncope and sudden cardiac death. In this report, we describe the clinical features, treatment, and clinical follow-up of three children with syncope associated with physical effort or emotion and cathecolaminergic polymorphic VT. Symptoms were controlled with beta-blockers, but one patient died suddenly in the fourth year of follow-up. Despite the rare occurrence, catecholaminergic polymorphic VT is an important cause of syncope and sudden death in children with no identified heart disease and normal QT interval.